2014
DOI: 10.1007/s11356-014-2592-6
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable chelating agents for industrial, domestic, and agricultural applications—a review

Abstract: Aminopolycarboxylates, like ethylenediaminetetraacetic acid (EDTA) and diethylenetriaminepentaacetic acid (DTPA), are chelating agents widely used in several industrial, agricultural, and domestic applications. However, the fact that they are not biodegradable leads to the presence of considerable amounts in aquatic systems, with serious environmental consequences. The replacement of these compounds by biodegradable alternatives has been the object of study in the last three decades. This paper reviews the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(126 citation statements)
references
References 67 publications
4
118
0
4
Order By: Relevance
“…Control (without metals supplementation) 372 ± 8 e 25% of optimal dosage 424 ± 11 14.0 ± 0.5 25% of optimal dosage þ EDDS 453 ± 14 21.8 ± 0.8 50% of optimal dosage 446 ± 16 19.9 ± 0.7 50% of optimal dosage þ EDDS 498 ± 16 33.9 ± 0.9 75% of optimal dosage 473 ± 21 27.2 ± 0.7 75% of optimal dosage þ EDDS 506 ± 19 36.0 ± 1.3 100% of optimal dosage 504 ± 18 35.5 ± 1.2 100% of optimal dosage þ EDDS 496 ± 19 33.3 ± 1.0 200% of optimal dosage 487 ± 14 30.9 ± 0.8 used for indirectly indicating the methanogenic activity of anaerobic sludge (Dong et al, 2010;Kida et al, 2001;Qing-Hao et al, 2008). Fig.…”
Section: Supplementation Of Trace Metalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Control (without metals supplementation) 372 ± 8 e 25% of optimal dosage 424 ± 11 14.0 ± 0.5 25% of optimal dosage þ EDDS 453 ± 14 21.8 ± 0.8 50% of optimal dosage 446 ± 16 19.9 ± 0.7 50% of optimal dosage þ EDDS 498 ± 16 33.9 ± 0.9 75% of optimal dosage 473 ± 21 27.2 ± 0.7 75% of optimal dosage þ EDDS 506 ± 19 36.0 ± 1.3 100% of optimal dosage 504 ± 18 35.5 ± 1.2 100% of optimal dosage þ EDDS 496 ± 19 33.3 ± 1.0 200% of optimal dosage 487 ± 14 30.9 ± 0.8 used for indirectly indicating the methanogenic activity of anaerobic sludge (Dong et al, 2010;Kida et al, 2001;Qing-Hao et al, 2008). Fig.…”
Section: Supplementation Of Trace Metalsmentioning
confidence: 99%
“…The chemical speciation of metals changes during complex chemical or biochemical reactions such as the precipitation withS 2À , CO 3 2À , PO 4 3À and the formation of inorganic and organic complexes, which might make metals not directly bioavailable and raise the cost of metals additive. The metals bound to chelating agent is reported as a feasible method to improve metals bioavailability to anaerobe via forming dissolved complexes and preventing metals precipitation (Hu et al, 2008a(Hu et al, , 2008bQing-Hao et al, 2008;Vintiloiu et al, 2013). Vintiloiu et al (2013) suggested that ethylenediaminetetraacetic acid (EDTA) could increase the solubility and bioavailability of essential metals, therefore enhance the methane production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EDTA has been used in several induced metal accumulation studies. The addition of EDTA to Pb spiked soil has been shown to increase the Pb content in Canavalia ensiformis and Helianthus annuus plants significantly [53,54]. Alternatively, a weak extraction of Pb using EDDS has been noted several times [35].…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained for MGDA and EDTA correspond to the literature data. The theoretical chemical simulations, which were performed at a 1:5 metal to chelating agent molar ratio, showed that at least 80% of Cu 2+ should be complexed by these compounds at a pH ranging from about 1.5 to 10.0 [27]. …”
Section: Resultsmentioning
confidence: 99%